2017
DOI: 10.1038/s41598-017-06557-6
|View full text |Cite
|
Sign up to set email alerts
|

Scenarios of polaron-involved molecular adsorption on reduced TiO2(110) surfaces

Abstract: The polaron introduced by the oxygen vacancy (Vo) dominates many surface adsorption processes and chemical reactions on reduced oxide surfaces. Based on IR spectra and DFT calculations of NO and CO adsorption, we gave two scenarios of polaron-involved molecular adsorption on reduced TiO2(110) surfaces. For NO adsorption, the subsurface polaron electron transfers to a Ti:3d-NO:2p hybrid orbital mainly on NO, leading to the large redshifts of vibration frequencies of NO. For CO adsorption, the polaron only trans… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
35
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(35 citation statements)
references
References 55 publications
0
35
0
Order By: Relevance
“…[1][2][3] However, considerably less is known about the other side of this interplay between adsorbates and defects, namely how adsorbates alter the distribution of defects at the surfaces of materials. 4,5 This is the issue we address in the current study through a detailed set of experiments and simulations of water on rutile TiO2, in which we focus on the interplay between water and excess electron defects.…”
Section: Table Of Contents (Toc) Graphicmentioning
confidence: 99%
“…[1][2][3] However, considerably less is known about the other side of this interplay between adsorbates and defects, namely how adsorbates alter the distribution of defects at the surfaces of materials. 4,5 This is the issue we address in the current study through a detailed set of experiments and simulations of water on rutile TiO2, in which we focus on the interplay between water and excess electron defects.…”
Section: Table Of Contents (Toc) Graphicmentioning
confidence: 99%
“…Simultaneously, reactant binding energy and efficiency of reactant dissociation can be enhanced. 10 , 27 30 Density functional theory (DFT) calculations conducted by the Liu group reported that EPs induced by titanium interstitials or single hydrogen atom preferred to reside in deeper inner layers when the surface was clean, while they tended to diffuse toward surface sites in the presence of adsorbed water or methanol. 9 , 30 The polaron–adsorbate interaction drove partial dissociations of the adsorbates on the reduced TiO 2 (110) surface.…”
Section: Introductionmentioning
confidence: 99%
“…Likewise, by combining IR spectroscopy and DFT calculations, Cao et al suggested transformation of sublayer polarons into surface polarons, induced by adsorption of CO and NO molecules. 27 A combined experimental/theoretical study of CO adsorbed on Ti-containing materials showed a complex photochemistry involving plasmons and polaronic effects. 31 …”
Section: Introductionmentioning
confidence: 99%
“…[21][22][23] Excess electrons are found to orig-inate mostly from surface defects, such as oxygen vacancies, Nb impurities, hydroxyl groups and interstitial titanium atoms. [23][24][25][26] Formation of polarons is particularly favorable at Ti 4+ sites in the near-surface region, 27 with consequent effects on the adsorption 28 and on the stability of the surface. At high reduction states, the strong polaronic repulsion was found to drive the surface from a (1×1) termination to a (1×2) reconstruction.…”
Section: Introductionmentioning
confidence: 99%